Біологічні особливості насіння лікарських рослин родини Lamiaceae в Лісостепу України - Porada, А.A.; Shevchenko, T.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Biological peculiarities of seed of 20 species of the medicinal plants of family Lаmiaceae are studied and their typical differences are determined. Germination and energy of germination these species, terms of storage are determined too.